2012
DOI: 10.1093/scan/nss096
|View full text |Cite
|
Sign up to set email alerts
|

Is it just a brick wall or a sign from the universe? An fMRI study of supernatural believers and skeptics

Abstract: We examined with functional magnetic resonance imaging the brain activity of 12 supernatural believers and 11 skeptics who first imagined themselves in critical life situations (e.g. problems in intimate relationships) and then watched emotionally charged pictures of lifeless objects and scenery (e.g. two red cherries bound together). Supernatural believers reported seeing signs of how the situations were going to turn out in the pictures more often than skeptics did. Viewing the pictures activated the same br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 55 publications
2
28
0
1
Order By: Relevance
“…In line with our predictions, multiple studies have identified left‐lateralized activity (based on inspection of the reported peaks) associated with reasoning about past events, making inferences about related sentences, attempting to generate explanations, and inferring a rule . Conversely, right‐lateralized activity has been observed when logic conflicts with prior beliefs, when participants are preparing for a set shift or receiving feedback necessitating such a shift, and generally in context monitoring and inhibition, including inhibiting outlandish hypotheses . However, most of this evidence is fairly qualitative and lacks direct contrasts between the hemispheres; there are also studies whose results seem to at least partially contradict our predictions …”
Section: Cognitive Neuroscience Studies In Healthy Adultssupporting
confidence: 83%
“…In line with our predictions, multiple studies have identified left‐lateralized activity (based on inspection of the reported peaks) associated with reasoning about past events, making inferences about related sentences, attempting to generate explanations, and inferring a rule . Conversely, right‐lateralized activity has been observed when logic conflicts with prior beliefs, when participants are preparing for a set shift or receiving feedback necessitating such a shift, and generally in context monitoring and inhibition, including inhibiting outlandish hypotheses . However, most of this evidence is fairly qualitative and lacks direct contrasts between the hemispheres; there are also studies whose results seem to at least partially contradict our predictions …”
Section: Cognitive Neuroscience Studies In Healthy Adultssupporting
confidence: 83%
“…In the social psychological literature an often-used paradigm is presenting participants with short vignettes to assess participants' implicit attitudes (Burstin, Doughtie, & Raphaeli, 1980), but also to directly simulate participants' responses to particular scenarios (Robinson & Clore, 2001). For instance, in a recent study participants were presented with short vignettes describing important life events and subsequently they were required to what extent they perceived a special meaning or message in a random picture (Lindeman, Svedholm, Riekki, Raij, & Hari, 2013). By using this methodology it was found that paranormal believers perceived more special messages in the pictures than skeptics -in line with the idea that paranormal believers imbue random stimuli with more meaning and more readily project illusory patterns in random noise (Riekki, Lindeman, Aleneff, Halme, & Nuortimo, 2013;van Elk, 2013).…”
Section: Experiments 6 81 Introductionmentioning
confidence: 94%
“…One behavioral feature that might facilitate social perception is the innate tendency to see agency and mental states in inanimate objects, even in moving geometrical shapes (Heider and Simmel, 1944). Assuming the world to be animated and full of agents is especially common in childhood; in adulthood, active inhibition of the attribution of agency seems to be required for rational inferences about events in the world (Lindeman et al, 2013).…”
Section: The Challenge Of Interpreting 2pn Datamentioning
confidence: 99%